ANALYSIS OF PROPERTIES OF CONCRETE USING MANUFACTURE SAND AS FINE AGGRIGATES - Gadgihalli, Vishal; Ramya; Babitha Rani; HavanjeDinakar, Raghavendra Prasad; Lohith (International Journal of Research -GRANTHAALAYAH, 2017)
Aggregate in concrete acts as structural filler, these place a crucial than simple statement implies it is the material that the cement paste coats and blind together. Now a day’s using river sand is prohibited by government, as these cause soil erosion. In this paper analysis of properties of concrete using manufacture sand as course aggregate is studied and verified the strength of concrete and temperature emitted due to chemical reaction to the normal Portland cement. Using manufacture sand as course aggregate the temperature emitted due to exothermal reaction of concrete has reduced. Although the compressive strength of the concrete has reduced compared to normal concrete where no admixtures were used to enhance the properties of concrete.